2007
DOI: 10.1289/ehp.10260
|View full text |Cite
|
Sign up to set email alerts
|

DDT and Breast Cancer in Young Women: New Data on the Significance of Age at Exposure

Abstract: BackgroundPrevious studies of DDT and breast cancer assessed exposure later in life when the breast may not have been vulnerable, after most DDT had been eliminated, and after DDT had been banned.ObjectivesWe investigated whether DDT exposure in young women during the period of peak DDT use predicts breast cancer.MethodsWe conducted a prospective, nested case–control study with a median time to diagnosis of 17 years using blood samples obtained from young women during 1959–1967. Subjects were members of the Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
289
0
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 401 publications
(311 citation statements)
references
References 33 publications
15
289
0
7
Order By: Relevance
“…Environmental contaminants, particularly those of the polycyclic aromatic hydrocarbon (PAH) and organochlorine (OC) groups of compounds, have been implicated in the aetiology of various cancers in humans [40][41][42], in laboratory animal models [43] and in wildlife [44][45][46]. These ubiquitous persistent pollutants, found in both the terrestrial and marine environments, have arisen through the widespread use of industrial chemicals such as the polychlorinated biphenyls (found in capacitors and transformers) and pesticides such as DDT.…”
Section: (C) Environmental Contaminantsmentioning
confidence: 99%
“…Environmental contaminants, particularly those of the polycyclic aromatic hydrocarbon (PAH) and organochlorine (OC) groups of compounds, have been implicated in the aetiology of various cancers in humans [40][41][42], in laboratory animal models [43] and in wildlife [44][45][46]. These ubiquitous persistent pollutants, found in both the terrestrial and marine environments, have arisen through the widespread use of industrial chemicals such as the polychlorinated biphenyls (found in capacitors and transformers) and pesticides such as DDT.…”
Section: (C) Environmental Contaminantsmentioning
confidence: 99%
“…The Child Health and Development Studies (CHDS) have found that women who have high levels of polychlorinated biphenyls (PCBs) in their blood immediately after giving birth have a tripled risk of developing breast cancer nearly two decades later 7 . The pesticide DDT has an even greater effect 8 .…”
Section: A Question Of Quantitymentioning
confidence: 99%
“…Some epidemiological evidence has been published on the link between human exposure to POPs and the risk of certain types of cancer (Boada et al, 2012;Brauner et al, 2012b;Cohn et al, 2012;Cohn et al, 2007;McGlynn et al, 2008;Recio-Vega et al, 2011;Xu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%